Analysis of the Influence of Design, Labor, Materials, and Equipment on Control Models, Time Performance, and Costs of Underground Foundation Works in Bridge Construction - Latif, Fatmawati; Suroso, Agus (Universitas Ibn Khaldun Bogor, 2025)
In the implementation of construction projects, it has been determined and limited by constraints that are mutually influencing and are commonly referred to as the project constraint triangle, namely the scope of work (scope), time, and cost, these three factors will determine the quality of a project. This study aims to analyze the Design, Labor, Materials, and Equipment Against the Time Performance Control Model and Cost of the Lower Foundation Work (Bore Pile) Bridge Project. The relationship between Design, Labor, and Materials is made a regression analysis with SPSS while the Time Performance Control Model and Cost of the Lower Foundation Work will be made in a path diagram model, and analyzed using SEM-PLS with a sample of 104 respondents. The study's results indicate that design, labor, materials, and equipment significantly influence the control model in bridge construction projects. The control model in bridge construction projects significantly impacts on-time performance and cost performance, design variables, labor, materials, and equipment are the key to improving the control model on-time performance and cost performance. The control model has an effect as a mediation of design, equipment, labor, and materials on cost performance and time performance.